Bridging the gap between field data and global models: current strategies in aeolian research - Joanna Bullard (2010)
Modern global models of earth-atmosphere-ocean processes are becoming increasingly sophisticated but still require validation against empirical data and observations. This commentary reports on international initiatives amongst aeolian researchers that seek to combine fi eld-based data sets and geomorphological frameworks for improving the quality of data available to constrain and validate global models. These include a second iteration of the Dust Indicators and Records from Terrestrial Marine Palaeoenvironments (DIRTMAP2) database, the Digital Atlas of Sand Seas and Dunefi elds of the World and a new geomorphologybased land surface map produced by the QUEST (Quantifying Uncertainties in the Earth System) Working Group on Dust.